Clinical Study of Chuanzi Moxibustion in Improving Neurogenic Bladder Function and Preventing Urinary Tract Infection after Spinal Cord Injury - Xia ZHOU; Xiangyu WANG; Xiangxia MENG; Jiale ZHANG; Liping SUN (康复学报)
Objective:To explore the clinical effect of Chuanzi moxibustion in the prevention and treatment of neurogenic bladder urinary tract infection caused by spinal cord injury.Methods:A total of 60 patients with highly compliant neurogenic bladder after complete spinal cord injury diagnosed in the Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine from January 2020 to December 2020 were selected and randomly divided into the control group and the treatment group, with 30 cases in each group. Routine treatment and nursing care were used in both groups. The treatment group was treated with Chuanzi moxibustion every other day combined with rubbing Wenyang Lishui agent(hospital protocol)for eight weeks. The bladder spontaneous urination volume, residual urine volume, urine routine, and the quality of life(QoL)index were observed and compared between the two groups as the efficacy assessment. Hamilton depression scale(HAMD-17)scores were used as the secondary efficacy assessment.Results:There were no significant differences in bladder residual urine volume, spontaneous urination volume, quality of life index, and HAMD-17 before treatment between the two groups. After treatment for eight weeks, bladder residual urine volume, spontaneous urination volume, QoL scores and HAMD-17 scores in both groups were significantly improved, and the differences were statistically significant than before treatment(P<0.05);two cases of urinary tract infection occurred in the treatment group, nine cases of urinary tract infection occurred in the control group, the number of urinary tract infection cases occurred in the treatment group was significantly less than that in the control group, and the differences were statistically significant(P<0.05);at the end of treatment, bladder residual urine volume, spontaneous urination volume, QoL scores and HAMD-17 scores in the treatment group were(82.53±33.78)mL, (237.23±30.66)mL, (4.13±0.78)scores and(6.10±1.90)scores, respectively, which were superior to(109.63±35.21)mL, (87.63±28.35)mL, (4.80±0.89)scores and(8.63±2.17)scores in the control group, and the differences were statistically significant(P<0.05).Conclusion:Chuanzi moxibustion can effectively improve bladder function of patients with spinal cord injury, such as reduce residual urine volume, increase spontaneous urination volume, reduce the occurrence of urinary system infection. It can also improve QoL of patients, relieve depression, and have better efficacy, with clinical promotion value.